2019
DOI: 10.3390/ijerph16173199
|View full text |Cite
|
Sign up to set email alerts
|

Co-Exposure to SiO2 Nanoparticles and Arsenic Induced Augmentation of Oxidative Stress and Mitochondria-Dependent Apoptosis in Human Cells

Abstract: Widespread application of silica nanoparticles (nSiO2) and ubiquitous metalloid arsenic (As) may increase their chances of co-exposure to human beings in daily life. Nonetheless, studies on combined effects of nSiO2 and As in human cells are lacking. We investigated the co-exposure effects of nSiO2 and As in human liver (HepG2) and human fibroblast (HT1080) cells. Results showed that nSiO2 did not cause cytotoxicity. However, exposure of As caused oxidative stress and apoptosis in both types of cells. Interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 56 publications
13
22
0
Order By: Relevance
“…Yang et al demonstrated that cardiac toxicity of MeHg was noticeably increased by Si NP exposure both in vitro and in vivo. Our recent study also demonstrated that Si NPs exacerbated the cytotoxicity of arsenic (As) in HepG2 cells and human fibroblasts (HT1080) . These results are in support of current findings that Si NPs have the potential to increase the toxic potential of ubiquitous heavy metals.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Yang et al demonstrated that cardiac toxicity of MeHg was noticeably increased by Si NP exposure both in vitro and in vivo. Our recent study also demonstrated that Si NPs exacerbated the cytotoxicity of arsenic (As) in HepG2 cells and human fibroblasts (HT1080) . These results are in support of current findings that Si NPs have the potential to increase the toxic potential of ubiquitous heavy metals.…”
Section: Resultssupporting
confidence: 86%
“…Limbach et al noted that Si NPs facilitates the cellular internalization of heavy metals such as manganese (Mn) or cobalt (Co). Our recent study also observed that Si NPs increased the uptake of arsenic (As) by HepG2 and HT1080 cells …”
Section: Resultsmentioning
confidence: 80%
“…For this reason, a deep understanding of combined NP exposures in a complex environment, such as the human body, is crucial. Many uptake studies have investigated the effect of one SiO 2 NP type [ 13 , 14 , 15 ] or its combination with other molecules [ 16 , 17 ], whereas studies on the combined effects of silica particles with different physicochemical properties, i.e., sizes, on human cells are lacking. It has been demonstrated that some NPs can be internalized faster when co-exposed due to the activation of multiple parallel endocytic pathways [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…We attempted similar experiments with B[a]P, but could not detect any genotoxic potential of this substance in RAW 264.7 cells. The synergistic interaction of SiO 2 particles with co-contaminants has been reported in various studies, particularly with metals, such as cadmium, methylmercury, arsenic, and lead [13,14,[40][41][42][43][44], or with B[a]P [10][11][12]. Increased genotoxic potential has been highlighted for SiO 2 and B[a]P in epithelial cells [10,11,44].…”
Section: Discussionmentioning
confidence: 94%
“…Synergistic interaction has also been reported between SiO 2 -NPs and lead acetate in A549 alveolar epithelial cells, causing mitochondria-dependent apoptosis [13]. Moreover, cytotoxicity, oxidative stress, and apoptosis were reported for arsenic when co-exposed with SiO 2 -NPs in HepG2 liver cells and fibroblasts [14]. Recently, Cao et al reported increased cytotoxicity, oxidative stress, and translocation of the fungicide boscalid upon co-exposure of in vitro intestinal epithelial models to the E551 food additive (SiO 2 ), previously submitted to an in vitro simulated digestion [15].…”
Section: Introductionmentioning
confidence: 84%